Habit Formation after Random Interval Training Is Associated with Increased Adenosine A2A Receptor and Dopamine D2 Receptor Heterodimers in the Striatum - He, Yan; Li, Yan; Chen, Mozi; Pu, Zhilan; Zhang, Feiyang; Chen, Long; Ruan, Yang; Pan, Xinran; He, Chaoxiang; Chen, Xingjun; Li, Zhihui; Chen, Jiang-Fan (Frontiers in Molecular Neuroscience, 2016)
Striatal adenosine A2A receptors (A2ARs) modulate striatal synaptic plasticity and instrumental learning, possibly by functional interaction with the dopamine D2 receptors (D2Rs) and metabotropic glutamate receptors 5 (mGluR5) through receptor-receptor heterodimers, but in vivo evidence for these interactions is lacking. Using in situ proximity ligation assay (PLA), we studied the subregional distribution of the A2AR-D2R and A2AR-mGluR5 heterodimer complexes in the striatum and their adaptive changes over the random interval and random ratio training of instrumental learning. After confirming the specificity of the PLA detection of the A2AR-D2R heterodimers with the A2AR knockout and D2R knockout mice, we detected a heterogeneous distribution of the A2AR-D2R heterodimer complexes in the striatum, being more abundant in the dorsolateral than the dorsomedial striatum. Importantly, habit formation after the random interval training was associated with the increased formation of the A2AR-D2R heterodimer complexes, with prominant increase in the dorsomedial striatum. Conversely, goal-directed behavior after the random ratio schedule was not associated with the adaptive change in the A2AR-D2R heterodimer complexes. In contrast to the A2AR-D2R heterodimers, the A2AR-mGluR5 heterodimers showed neither subregional variation in the striatum nor adaptive changes over either the random ratio (RR) or random interval (RI) training of instrumental learning. These findings suggest that development of habit formation is associated with increased formation of the A2AR-D2R heterodimer protein complexes which may lead to reduced dependence on D2R signaling in the striatum.